The Challenges of Training Undergraduate Clinical Surgical Students: A Study experience after Six Years in The New School of Medicine in Ndola, Zambia. - Mugala, Duncan D; Kawimbe, Boniface (Advances in Social Sciences Research Journal, 2017)
The training of Medical students is always a challenge. Our students have to pass through the school of medicine for a period of five years in which they have tests, assignments and ends of terms and years examinations. We have learned from what Hafferty F.W wrote and proposed that the medical school should be best thought of as a 'learning environment' and that reform initiatives must be undertaken with an eye to what students learn instead of what they are taught[1]. We have learned a lot from our students as we have gone through six years when the school was opened. It has been said that innovative approaches to teaching, progressive skills instruction, assessment and examination and support of the development of professionalism, require us as teachers should have the time to observe, instruct, coach, and assess our students and we should also have time for self-reflection and our own professional development[6].These have been our responsibility. But have we acquired these standards?